"Semio-Phonological Approaches in Teaching Tajweed: A Study of Articulation Points and Characteristics" - biba, alia (El Omda in Linguistics and Discourse Analysis, 2018)
The science of Tajweed is concerned with the correct pronunciation of the words of the Qur'an, which requires knowledge of the origins of sounds in terms of their articulation points, characteristics, and the organs from which they are produced. This means that the science necessitates giving each letter its due in terms of its articulation and attribute. Therefore, the strategy for teaching this science requires understanding its procedural mechanisms within the linguistic field, especially since this science depends on pronunciation. This study includes teaching the articulation points and the letters associated with this science using modern techniques, blending both linguistic and non-linguistic approaches. In other words, it integrates the spoken with the visual through a CD titled "The Tale of Tajweed." This study will explore the main methods and tools used to teach this science, including light and sound effects, symbols, and more. Additionally, it will discuss how this science influences phonetic studies on one hand and linguistic and semiotic studies on the other.